Integrative taxonomic revision concerning phylogenetic relationships, morphological variation, distribution, ecology and conservation of Gagea alberti (Liliaceae) within its natural range - Serik Kubentayev; Igor Levichev; Marcin Nobis; Shukherdorj Baasanmunkh; Ewelina Klichowska; Aidyn Orazov; Daniyar Alibekov; Balsulu Kubentayeva; Hyeok Jae Choi (Botanical Studies)
Abstract Background The genus Gagea is one of the largest and most complex members of the family Liliaceae, and comprises more than 320 species. Gagea is taxonomically challenging because of its morphological variations, polyploidization, hybridization and potential to inhabit ecologically diverse environments. In this study, we investigated the taxonomy, morphology, conservation, distribution and phylogeny, of Gagea alberti across within its natural range. Results Gagea alberti iswidely distributed in Kazakhstan, Kyrgyzstan, southern Russia, western China, and Mongolia. This species exhibited high ecological plasticity and phenotypic variability. Based on extensive morphological and phylogenetic analyses, we treated G. altaica and G. sarysuensis as synonyms of G. alberti. The conservation status of this species was assessed as least concern (LC) at a global level. We provide detailed analytical and morphological illustrations of the ontogeny of G. alberti. Furthermore, we provide a checklist of section Plecostigma, including G. alberti, along with a brief morphological description of the section. Conclusions This study provided new insights into the morphology, phylogeny, and distribution of G. alberti, a species characterized by high ecological plasticity and phenotypic variability. The high ecological plasticity and phenotypic variability of G. alberti are the results of a long-term evolutionary process that enabled the species to adapt to a wide range of environmental conditions.